Antioxidant status in rabbit aqueous humor after instillation of ascorbyl laurate-based nanostructures - Angel Villegas, Natalia (2019)
The aim of this work was evaluate the antioxidant effect of ascorbyl laurate (ASC12) based nanostructures applied topically to the cornea of ocular normotensive and hypertensive rabbits. The ASC12 was chosen for its capacity to form liquid lyotropic crystal and keeps its free radical trapping power.MethodsThe hypertension model was performed in six rabbits and was obtained by the application of intracameral injections of alpha-chymotrypsin in the right eye. A single 50 mL dose of ascorbyl laurate coagel 2% w/v (COA-ASC12) was applied topically to the cornea of six normotensive and six hypertensive rabbits. The aqueous humor samples were obtained before and after instillation of COA-ASC12 at different times (2 h and 4 h). Antioxidant capacity was determined via the reduction reaction with iron and tripyridyltriazine (FRAP) and the total proteins were measured using the Bradford reagent.ResultsThe kinetic antioxidant capacity in the aqueous humor of normotensive and hypertensive rabbits showed a maxim increment at 4 hours instillation. Also, the antioxidant capacity in the aqueous humor of hypertensive rabbits was ten times lower than in normotensive rabbits. This type of nanostructures has the potential to significantly improve the topical formulation for the prophylaxis and treatment of several eye diseases.